Icelandic-Canadian memory lore - Magnús Einarsson (Paper (Canadian Centre for Folk Culture Studies), 1992)
A selection of 332 examples of Icelandic traditional poetry and other bound language contains children's rhymes, rigmaroles, riddles, lullabies and prayer verses, as well as adult lore such as dance and drinking songs, religious and humorous poems plus proverbs and syayings.